1987
DOI: 10.1177/0739456x8700600308
|View full text |Cite
|
Sign up to set email alerts
|

Urban Cultivation Amidst Modernization: How Should We Interpret It?

Abstract: Many African cities are currently marked by the decline of the formal urban economy and the simultaneous upsurge of household cultivation by the urban poor. This has generated two types of critical responses, though for very different reasons. The modernization proponents view urban cultivation as a manifestation of rural habits, predominantly relied upon by recent migrants lacking integration into the urban economy and culture. The New-Marxist critics, on the other hand, blame such activities for contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Indeed, Gefu (1992, 301) has observed that urban agriculture has increased in Nigeria to supplement declining real urban wages 'despite the evident diseconomies of scale and low profit margins'. Downloaded by [The University of Manchester Library] at 04:07 08 December 2014 These views, however, have been refuted by others who have noted both the prevalence and resilience of urban agriculture in African cities, as well as the importance of subsistence food production in circumstances where up to three-quarters of the urban poor's income may be spent on food purchases (Sanyal, 1987;Mosha, 1991;Drakakis-Smith 1991;Memon & Lee-Smith, 1993;Egziabher et al, 1994;Maxwell, 1996). In a survey of six towns in Tanzania, Mlozi et al (1992) observe that urban agriculture is seen by people as a sound cash-saving strategy for households, releasing money that can then be spent elsewhere within the household's consumption patterns.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Indeed, Gefu (1992, 301) has observed that urban agriculture has increased in Nigeria to supplement declining real urban wages 'despite the evident diseconomies of scale and low profit margins'. Downloaded by [The University of Manchester Library] at 04:07 08 December 2014 These views, however, have been refuted by others who have noted both the prevalence and resilience of urban agriculture in African cities, as well as the importance of subsistence food production in circumstances where up to three-quarters of the urban poor's income may be spent on food purchases (Sanyal, 1987;Mosha, 1991;Drakakis-Smith 1991;Memon & Lee-Smith, 1993;Egziabher et al, 1994;Maxwell, 1996). In a survey of six towns in Tanzania, Mlozi et al (1992) observe that urban agriculture is seen by people as a sound cash-saving strategy for households, releasing money that can then be spent elsewhere within the household's consumption patterns.…”
mentioning
confidence: 91%
“…Some observers have developed the argument that urban farming reduces the social costs of labour reproduction by transferring the burden of maintaining the labour force from the state to labour itself, hence driving down labour costs (Rakodi, 1985;Freeman, 1991). This view has been criticised by Sanyal (1987), however, arguing that the state has consistently opposed urban agriculture through legislation and, if necessary, force. Indeed, it can be further argued that such postcolonial legislation is itself a hangover from colonial planning principles.…”
mentioning
confidence: 95%
See 3 more Smart Citations